Rewind: Cbt-Based Serious Game To Improve Cognitive Emotion Regulations And Anxiety Disorders - Heng, Yew Ken (2023)
ReWIND is a CBT-based serious game designed specifically to improve cognitive emotion regulations and anxiety disorders of patients. The main objective of the study is to design a story-driven serious game to facilitate cognitive behavioural therapy (CBT) and measure its efficacy to complement the treatment for anxiety disorders. The foundation of the game storylines focuses on three cognitive emotion regulation strategies common in anxiety disorders: catastrophizing, rumination, and lack of refocus on planning. Each strategy consists of two scenarios remodelled from real-life incidents following Ellis’ ABCDE-model (activating event, belief, consequence, disputation, and effect). A three-phase methodology is presented in this study covering the storyline development, game development, and experimental design in detail. The mixed-design ANOVA model is used to assess the overall performance of ReWIND and test the hypotheses regarding its capability to reduce participants’ anxiety symptoms and improve cognitive emotion regulations. The outcome of this study is satisfactory as ReWIND is capable of reducing the severity level of anxiety symptoms and trait anxiety levels while increasing perceived control of anxiety better than the non-interactive task.